Rhodium catalyzed C–C bond cleavage/coupling of 2-(azetidin-3-ylidene)acetates and analogs. Issue 84 (7th October 2019) - Yang, Xuan; Kong, Wei-Yu; Gao, Jia-Ni; Cheng, Li; Li, Nan-Nan; Li, Meng; Li, Hui-Ting; Fan, Jun; Gao, Jin-Ming; Ouyang, Qin; Xie, Jian-Bo
Abstract : The tandem "conjugate addition/β-C cleavage/protonation" process (CCP) is reported. Abstract : The C–C bond cleavage/coupling of 2-(azetidin-3-ylidene)acetates with aryl boronic acids catalyzed by a rhodium complex was studied with a "conjugate addition/β-C cleavage/protonation" strategy.